2019
DOI: 10.1101/839985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanocomposite bioink exploits dynamic covalent bonds between nanoparticles and polysaccharides for precision bioprinting

Abstract: The field of bioprinting has made significant recent progress towards engineering tissues with increasing complexity and functionality. It remains challenging, however, to develop bioinks with optimal biocompatibility and good printing fidelity. Here, we demonstrate enhanced printability of a polymer-based bioink based on dynamic covalent linkages between nanoparticles (NPs) and polymers, which retains good biocompatibility. Amine-presenting silica NPs (ca. 45 nm) were added to a polymeric ink containing oxidi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The 3D-printing platform of regenHU offered the necessary technological instrumentation and flexibility to implement our manual protocols in an automated assembly system. The pre-existing platform consisted of a microvalve inkjetting device suitable for printing cells, [47][48][49][50][51][52] for example keratinocytes and melanocytes. We modified the platform by the addition of two new modules for our specific needs to establish the SkinFactory: The first module is made up of a piston-driven extrusion tool, which utilizes a double syringe and a mixer tip for combining collagen and cells (fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…The 3D-printing platform of regenHU offered the necessary technological instrumentation and flexibility to implement our manual protocols in an automated assembly system. The pre-existing platform consisted of a microvalve inkjetting device suitable for printing cells, [47][48][49][50][51][52] for example keratinocytes and melanocytes. We modified the platform by the addition of two new modules for our specific needs to establish the SkinFactory: The first module is made up of a piston-driven extrusion tool, which utilizes a double syringe and a mixer tip for combining collagen and cells (fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of a given bioink to counter gravity can be quantitatively evaluated through printing a filament over a pillar array, bridging a gap at increasing distance, e.g., as previously reported with gap sizes ranging between 1–12 mm and measuring the angle of deflection 78 , 172 or the area below the filament. 42 , 174 The angle of deflection θ, expressed as a function of the gap distance, is a measure of the deformation suffered by the filaments due to the discrepancy between the gravitational force given by the filament’s own weight, and inertia measured by yield stress and storage modulus of the ink. In particular, yield stress was suggested as predictor of potential filament deformation as increasing values for this parameter correlated with lower deflection angle values.…”
Section: Assessment Of Printability and Shape Fidelitymentioning
confidence: 99%
“…Poor or slow stabilization of the ink after dispensing, as well as fusion of adjacent filaments are in fact marked by the collapse of the filament circularity. 78 , 174 Semiquantitative evaluation, based on the circularity of printed filaments and shape fidelity of the pore, was recently introduced. 46 , 140 Using this approach, a printability index ( P r ) which is based on the perimeter and area of the pore can be easily derived ( Figure 6 Biii).…”
Section: Assessment Of Printability and Shape Fidelitymentioning
confidence: 99%
“…Comparative studies between bioinks loaded with different amounts of nanoparticles demonstrated that they could improve the bioinks mechanical properties. Recently, Lee and colleagues assessed the incorporation of aminopropyl-modified silica nanoparticles into an oxidized alginate bioink [89]. The particles were linked by reversible imine bonds, allowing the creation of a dynamic polymer with thixotropic and self-healing properties.…”
Section: Nanocompositesmentioning
confidence: 99%